Metabolic assessment of the use of probiotic or monensin in lambs kept in semi-confined conditions - Tabeleão, Vinicius Coitinho; Schwegler, Elizabeth; Moura, Sandra Vieira de; Goulart, Maikel Alan; Weiser, Mariane Aline; Silva, Viviane Maciel da; Roos, Talita Bandeira; Del Pino, Francisco Augusto Burket; Gil-Turnes, Carlos; Braunes, Cassio Cassal; Corrêa, Marcio Nunes (Semina: Ciências Agrárias, 2014)
The objective of this study was to verify probiotics and monensin effects on metabolic parameters in weaning lambs. In the experiment 1, thirty lambs divided in three groups were fed during 6 weeks. The lambs were enrolled in one of the following treatments: GC1: as a control, GB1: Bacillus cereus var. toyoi (1x106 spores/g) and GS1: Saccharomyces boulardii (1x106 viable cells/g). In the experiment 2, thirty lambs divided in three groups were fed during 8 weeks. The treatments consisted in GC2: as a control, GM2: monensin (500g/t) and GS2: Saccharomyces boulardii (1x106viable cells/g). In both experiments blood samples were collected weekly aiming to measure metabolic parameters as glucose, triacylglycerol (TAG), cholesterol, albumin, urea, aspartate amino transferase (AST), creatinine kinase (CK) and gamma glutamil transferase (GGT). The results from experiment 1 demonstrated that GS1 had greater (P<0.05) concentrations of albumin and urea during the adaptation period. In the postadaption period the GC1 demonstrated increased (P<0.05) concentrations of cholesterol, albumin and AST activity, in contrast, reduced (P<0.05) concentrations of glucose, urea and CK in comparison to GS1. However, during experiment two throughout the adaptation period the GS2 had greater (P<0.05) concentrations for albumin and urea. The GM2 had greater (P<0.05) concentrations for TAG and lower (P<0.05) for glucose and CK activity. During the post-adaption period the GS2 showed the lowest (P<0.05) concentrations for cholesterol and GGT activity, GC2 had greater (P<0.05) levels of albumin and AST activity as well as lower concentrations for urea. The GM2 had greater levels for GGT activity and lower levels for CK activity. Therefore, it is concluded that protein metabolism in lambs has better performance when Saccharomyces boulardii is added in the ration during the adaptation period. However, during post-adaptation period, monensin is more beneficial for the protein metabolism, once it does not interfere in the muscles catabolism.